Mapping and Evaluating the Attractiveness of Pilgrim Routes from an Experiential Perspective the Case of the ‘Paths through Italy’ - Forlani, Fabio; Ferrucci, Luca; Picciotti, Antonio; Splendiani, Simone (2021)
The assessment of tourist offerings and the attractiveness of tourist destinations has been the subject of many studies in the tourism management literature over the years. Several authors have examined the territorial characteristics and factors that nurture tourist destination attractiveness in order to create flexible models that are capable of providing recommendations and instructions for destination management policies in the tourism industry. However, one of the fields in which this topic has so far been under-studied is with regard to pilgrim routes. Calling upon the ‘Atlas of the Paths through Italy’ which represents the official census or count of Italian routes published and recognised by the Ministry of Environmental, Cultural and Tourism Heritage (MiBACT) in 2016, the purpose of this article is to compare all the ‘Paths through Italy’ and classify them according to their expressed or unexpressed tourism potential. In particular, through an experiential approach and the use of Fuzzy Set Ideal Type Analysis (FSITA) methodology, this article aims to evaluate the attractiveness of the Paths in terms of their structural capability, create a taxonomy of the Paths, identify the most attractive type of Path which should be taken as a best practice benchmark, and provide managerial and policy suggestions to improve the attractiveness of the weaker Paths. The results of the analysis found that three Paths had strong potential and six Paths had good potential for tourism development. This study provides both a descriptive framework and an interpretative approach to the Italian Paths to help public intuitions manage and develop policies for the sustainable development of these pilgrimage routes.
Keywords: FSITA; Paths through Italy; experiential tourism; pilgrim routes; slow tourism